Integrative phylogenetic analysis of the genus Episoriculus (Mammalia: Eulipotyphla: Soricidae) - Yingxun Liu; Xuming Wang; Tao Wan; Rui Liao; Shunde Chen; Shaoying Liu; Bisong Yue (PLoS ONE, 2025)
Shrews in the genus Episoriculus are among the least-known mammals in China, where representatives occur mainly in the Himalayan and Hengduan mountains. We sequence one mitochondrial and three nuclear genes from 77 individuals referable to this genus, collect morphometric data for five shape and 11 skull measurements from 56 specimens, and use museum collections and GenBank sequences to analyze phylogenetic relationships between this and related genera in an integrated molecular and morphometric approach. Whereas historically anywhere from two to eight species have been recognized in this genus, we conclude that six ( Episoriculus baileyi , E . caudatus , E . leucops , E . macrurus , E . sacratus , E . soluensis ) are valid. We dissent from recent systematic reviews of this genus and regard E . sacratus to be a valid taxon, E . umbrinus to be a subspecies of E . caudatus , and transfer E . fumidus to Pseudosoriculus . Our record of E . soluensis is the first for China, and expands the previously recognized distribution of this taxon from Nepal and NE India into the adjacent Yadong and Nyalam counties. One further undescribed Episoriculus taxon may exist in Xizang.